Adaptation to divergent larval diets in the medfly, Ceratitis capitata. (1st February 2017) - Leftwich, Philip T.; Nash, William J.; Friend, Lucy A.; Chapman, Tracey
Abstract: Variation in diet can influence the timing of major life‐history events and can drive population diversification and ultimately speciation. Proximate responses of life histories to diet have been well studied. However, there are scant experimental data on how organisms adapt to divergent diets over the longer term. We focused on this omission by testing the responses of a global pest, the Mediterranean fruitfly, to divergent selection on larval diets of different nutritional profiles. Tests conducted before and after 30 generations of nutritional selection revealed a complex interplay between the effects of novel larval dietary conditions on both plastic and evolved responses. There were proximate‐only responses to the larval diet in adult male courtship and the frequency of copulation. Males on higher calorie larval diets consistently engaged in more bouts of energetic courtship. In contrast, following selection, larval development time, and egg to adult survival showed evidence of evolved divergence between diet regimes. Adult body size showed evidence for adaptation, with flies being significantly heavier when reared on their "own" diet. The results show the multifaceted responses of individuals to dietary selection and are important in understanding the extreme generalism exhibited by the medfly.